Power coordinated control method with frequency support capability for hybrid single/three‐phase microgrid. Issue 10 (28th March 2018) - Zhou, Xiaoping; Chen, Yandong; Zhou, Leming; Luo, An; Guerrero, Josep M.; Wu, Wenhua; Yang, Ling; Tan, Wenjuan
Abstract : Due to the intermittent output power of distributed generations (DGs) and the variability of loads, voltage fluctuation and three‐phase power imbalance easily occur when hybrid single/three‐phase microgrid operates in islanded mode. To address these issues, the power exchange unit (PEU) and energy storage unit (ESU) are added into hybrid single/three‐phase microgrid, and a power coordinated control method with frequency support capability is proposed for hybrid single/three‐phase microgrid in this study. PEU is connected with three single‐phase microgrids to coordinate power exchange among three phases and provide frequency support for hybrid microgrid. Meanwhile, a power coordinated control method based on the droop control is proposed for PEU to alleviate three‐phase power imbalance and reduce voltage fluctuation of hybrid microgrid. Besides, ESU is injected into the DC‐link to buffer the system power fluctuation when DGs or loads suddenly change. The hierarchical control method is proposed for ESU to stabilise the DC‐link voltage and reasonably allocate the net exchanged power of PEU. Considering the collaboration between PEU and ESU, the state of charge of ESU is proposed to adjust the power transmission coefficient of PEU. The validity of the proposed control method has been verified by simulation and experiment.